COGNITIVE-STYLE APPROACH TO PSYCHOLOGICAL SUPPORT OF THE GIFTED PUPILS MOUNTAIN SCHOOLS OF THE UKRAINIAN CARPATHIANS - Anatoliy Paliy (Vasyl Stefanyk Precarpathian National University, 2015)
The differential-cognitological point of view, giftedness is "a systemic quality of a personality that develops throughout life and determines their abilities to achieve exceptionally high results in one or more activities compared to those of other people". Herewith, it is the fundamental concept of general aptitude, under which "the level of general abilities development that determines the range of activities in which a person can achieve great success" is understood. Within the structure of general aptitude intellectual giftedness is singled out as the level of development, as well as the type of organization of individual mental experience, which ensure an opportunity of creative intellectual activity, i. e. an activity, related to the creation of subjectively and objectively new ideas, to the use of innovative approaches to solving problems and openness to controversial aspects of the situation and so on. In order to identify talented children and adults the value of intellectual quotient (IQ) is still most commonly used. Psychometric approach (the measurement of psychic phenomena with the help of standardized IQ tests) to the diagnosis of intellectual giftedness, which is dominant in psychological diagnostics today, by definition, cannot "measure" the phenomena of an individual psyche, since the modern level of psychological science does not allow to proceed to psychological diagnosis, let alone prediction of a certain person`s behavior, on the basis of individual results in performing a psychological test (psychometric test of intelligence, personality questionnaire, projective methods etc). In our opinion, many problems in psychological and pedagogical support of gifted children could be avoided by making use of cognitive-style approach to diagnosis of intellectual giftedness, creative abilities, propensities and peculiar mental traits of a separate individuality. Objectivity of such an approach is corroborated by the results of individual cognitive styles (hereinafter CS) diagnostics, carried out by means of experimental techniques. In contrast to standardized tests, such techniques allow to perform diagnostic tests individually and reveal the peculiarities of the arrangement and functioning of an individual mind. Obviously, nowadays we are faced with the need for providing theoretical, methodological and empirical grounds for the development of a conceptual model that would consider giftedness as an integral psychological system, all aspects of which could be understood in the context of age dynamics and mental experience of an individual. CS approach to interpreting and diagnosis of giftedness provides a reliable theoretical basis for working out a systematic methodology of psychological diagnostics of the general aptitude, as it meets the basic principles of humanization of the educational environment in Ukraine. CS approach is child-centered, therefore, it brings in focus individual uniqueness and originality of each child.